Nísia Floresta: memória e história da mulher intelectual oitocentista - Battistella, Laura Sánchez Pereira (2017)
The present dissertation aims to problematize the female reality in the nineteenth century, from the life and work of the educator Nísia Floresta (1810-1885), who is considered, by the gender studies, one of the first Brazilian feminists. Thus, the prism of this research focuses on the nineteenth century woman versus a society of deeply patriarchal foundations that prevented her from revealing herself as a person with free will and, in a more specific way, this work deepens this question from the point of view of a woman who longed to manifest her intellectuality. Therefore, Intellectual History has been the theoretical choice chosen at the glimpse of nineteenth-century history, through the letters and life study of the Brazilian writer and educator Nísia Floresta. In the course of the study of the Nisian texts, we find historical evidence that allows us to analyze the condition of nineteenth-century women, specifically the intellectual woman. Thus, this research is permeated by considerations about the past and may still lead the reader to reflect on the extent to which this past still infers in our present.